Deciphering the mechanism of nano-enhanced docosahexaenoic acid accumulation in microalgae - Adamu Yunusa Ugya; Hui Chen; Qiang Wang (Journal of CO2 Utilization, 2025)
Docosahexaenoic acid (DHA) is a vital bioresource for human health due to its cardiovascular function, anti-inflammatory significance, and cognitive benefits. But the sustainability of DHA from its traditional sources is in question due to overfishing and environmental concerns. Microalgae is a sustainable alternative source of DHA; however, scale-up production of DHA from microalgae is strained due to the high cost of cultivation and extraction processes. This review provides an important insight into how nanoparticles can be used to enhance DHA biosynthesis in microalgae through targeted and efficient manipulation of cellular processes. The review shows that the manipulation of nanoscale material allows for intervention that improves the bioprospecting potential of microalgae through enhancing cultivation efficiency. Also, the mechanistic pathways through which nano-enhancement tends to upsurge DHA accumulation in microalgal systems were explored. The review indicates that nano-enhancements can be achieved through a complex mechanism that involves nanoparticles acting as growth promoters and biostimulants. Nanoparticles also enhance DHA in microalgae by triggering enhanced light utilization and plasmonic effects. Nanoparticles also play a critical role in increasing extraction efficiency and stability of DHA in microalgae, making them a promising tool for bioprospecting. But despite the significance of nanoparticles in enhancing DHA accumulation, limitations such as the high cost of nanomaterials and formulation, potential toxicity to microalgal cells, and limited understanding of nano-bio interactions hinder the achievement of scale-up application. Thus buttressing the need for further studies to address these challenges and optimize the use of nanoparticles in microalgae cultivation.